Reel Evil: A Critical Reassessment of Found Footage Horror. Issue 2 (1st November 2015) - Unknown
Abstract : The aim of this article is twofold. On the one hand, it offers a survey of found footage horror since the turn of the millennium that begins with The Blair Witch Project (1999) and ends with Devil's Due (2014). It identifies notable thematic strands and common formal characteristics in order to show that there is some sense of coherence in the finished look and feel of thefi lms generally discussed under this rubric. On the other hand, the article seeks to reassess the popular misunderstanding that found footage constitutes a distinctive subgenre by repositioning it as a framing technique with specific narrative and stylistic effects.